Upaya Meningkatkan Prestasi Siswa dalam Gerak Dasar Permainan Bola Basket dengan Teknik Bermain Lempar Tangkap Bola Tenis pada Siswa Kelas IX Semester 1 di SMP Negeri 1 Praya Timur Lombok Tengah - Rahban Rahban (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
Classroom Action Research with 2 cycles to find out whether the Application of Tennis Ball Throwing Game Can Improve Student Achievement In Basic Motion of Basketball Game on Grade IX Students of Semester 1 at SMP Negeri 1 East Praya, through descriptive approach qualitative, data collection method used observation, interview, and documentation. Student learning outcomes cycle I average 70.0 classical completeness 61.54%. Cycle II average learning outcomes 85.4 classical completeness 88.46%. So the Application of Games Throwing Ball Tennis In Basic Motion of Basketball Game on Class IX Students at SMP Negeri 1 East Praya can improve Learning Achievement.